Gospodarka agroturystyczna – aspekty ekonomiczne i zarządcze - Feczko, Janusz (Przedsiębiorczość - Edukacja, 2010)
Through lack of agritourism realistic knowledge are important present and future original research by Association of Tourism, Hotel and Gastronomy Education and Research, in the economic and management fields. Świętokrzyskie (Poland) region to has ready tourism potential. It is needed the creative development of agritourism farms management. The goverumental and territorial administration, and the other organization support has to be optimized.